Asnād-i asāsī-i plīnūmʹhā-yi Kumītah-i Markazī-i Ḥizb-i Dimūkrātik-i Khalq-i Afghānistān (Shuʻbah-i Tablīgh, Tarvīj va Āmūzish-i Kumītah-i Markazī-i Ḥ.D. Kh. A., 1981)
On the first six plenary sessions of the Central Committee of the Ḥizb-i Dimūkrātik-i Khalq-i Afghānistān.